2022
DOI: 10.3389/fcvm.2022.1033660
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HDL cholesterol, particles, and function associate with pediatric COVID-19 severity

Abstract: BackgroundMyriad roles for high-density lipoprotein (HDL) beyond atheroprotection include immunologic functions implicated in the severity of coronavirus disease-2019 (COVID-19) in adults. We explored whether there is an association between HDL and COVID-19 severity in youth.MethodsA pediatric cohort (N = 102), who tested positive for COVID-19 across a range of disease manifestations from mild or no symptoms, to acute severe symptoms, to the multisystem inflammatory syndrome of children (MIS-C) was identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…GlycA is also associated with disease severity in pediatric patients with COVID-19. Similar to those with Kawasaki disease, children with multisystem inflammatory syndrome of children (MIS-C) due to SARS-CoV-2 infection also have extremely high levels of GlycA [40]. GlycA levels were also remarkably high in patients with AP in our study, much higher than had been observed in other studies except in studies of adults with sepsis.…”
Section: Discussionsupporting
confidence: 74%
“…GlycA is also associated with disease severity in pediatric patients with COVID-19. Similar to those with Kawasaki disease, children with multisystem inflammatory syndrome of children (MIS-C) due to SARS-CoV-2 infection also have extremely high levels of GlycA [40]. GlycA levels were also remarkably high in patients with AP in our study, much higher than had been observed in other studies except in studies of adults with sepsis.…”
Section: Discussionsupporting
confidence: 74%
“…We found profound changes in lipid metabolism, consistent with previous studies 22 , 23 Lipid mediators have been described to be involved in vasodilation and increased vascular permeability 24 , a frequent and severe clinical manifestation of MIS-C 6 . Further, the unsupervised protein-protein co-expression network analyses conducted by machine learning indicated an intricate connection between apolipoproteins and immune dysregulation, which may be due to the function of lipids as proinflammatory mediators, as described in other conditions 25 .…”
Section: Discussionsupporting
confidence: 92%
“…This lipoprotein can induce a progression of atherosclerotic lesion formation (Julius et al 2022 ). A decrease in apolipoprotein A1 was associated with increased clinical severity in COVID-19 (Mietus-Snyder et al 2022 ). In addition, other lipid particles, including total, large, and small HDL particles, as well as HDL functional cholesterol efflux capacity, were related to the severity of COVID-19 among pediatric patients (Mietus-Snyder et al 2022 ).…”
Section: Pathogenic Mechanisms Of Cardiovascular Damage In Covid-19mentioning
confidence: 99%